2022
DOI: 10.1177/02184923221133956
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular solutions for abdominal aortic aneurysms: A comparative review of clinical outcomes with custom-made endografts

Abstract: Background The introduction of endovascular aortic repair has revolutionised the treatment of abdominal aortic aneurysms, replacing open surgical repair for the majority of elective cases due to its optimal morbidity and mortality. Several endovascular aortic repair stent grafts exist commercially, one of which is the Fenestrated Anaconda™ by Terumo Aortic which benefits from a very innovative design, unique custom-made approach and highly favourable results. Aims The main scope of this narrative review is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…58 All the above evidence, in addition to our results as well as the results of recent studies, unequivocally suggest that the Fenestrated Anaconda™ is the primary EVAR device choice for achieving long-term patient longevity and favourable late clinical outcomes, particularly survival, TVP, endograft migration and reintervention. [59][60][61] However, studies directly comparing endografts under similar clinical circumstances are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…58 All the above evidence, in addition to our results as well as the results of recent studies, unequivocally suggest that the Fenestrated Anaconda™ is the primary EVAR device choice for achieving long-term patient longevity and favourable late clinical outcomes, particularly survival, TVP, endograft migration and reintervention. [59][60][61] However, studies directly comparing endografts under similar clinical circumstances are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the findings in this review, it can be suggested that the Anaconda may achieve the most optimal sac regression relative to market competitors. To lend further evidence in support of the Anaconda, a recent scoping review by Jubouri et al 62 compared Anaconda with Zenith, highlighting a wide variety of clinical outcomes achieved using both devices. The authors clearly concluded that the Anaconda can be considered the superior EVAR 2022 Cross-sectional international analysis 5058 Anaconda A sac regression of 0-30% was observed in 4772 (94.3%) patients over the first four years post-EVAR.…”
Section: Evar Devices and Sac Regressionmentioning
confidence: 99%